1989
DOI: 10.1016/0020-7292(89)90606-1
|View full text |Cite
|
Sign up to set email alerts
|

The intramural segment and the uterotubal junction: an anatomic and histologic study

Abstract: The injected latex method was used to study the anatomy of the intramural segment in ten uteri. Another ten uteri were used for its histological evaluation. The intramural segment had an S-shaped course with double curves. Its length ranged between 0.9 and 1.7 cm. The lining epithelium showed variations at different levels with increase in cell density and number of cilia as the isthmus was approached. At the uterotubal junction, there were mucosal folds of endosalpinx directed towards the tubal lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…A previous study reported an endosalpinx without mucosal folds, but this observation may be because of the limitations in histological techniques [19]. Similar to the results of the present study, a previous study describing the shape of the mucosa of the uterine segment showed the mucosa folded toward its base as tongue-like processes [20]. These folds form crypts at the beginning of the lumen and are easily observed in 3D reconstructions.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study reported an endosalpinx without mucosal folds, but this observation may be because of the limitations in histological techniques [19]. Similar to the results of the present study, a previous study describing the shape of the mucosa of the uterine segment showed the mucosa folded toward its base as tongue-like processes [20]. These folds form crypts at the beginning of the lumen and are easily observed in 3D reconstructions.…”
Section: Discussionsupporting
confidence: 81%
“…A transitional area is also apparent in humans. Here the simple cuboidal epithelium present in the vicinity of the uterine ostium changes to the simple columnar epithelium of the endometrium together with the appearance of uterine glands (Rocca et al, ). Similarly, uterine glands make their appearance in the transition zone in the bovine (Wrobel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the human (Rocca et al, 1989), bovine (Wrobel et al, 1993), rat, sheep, and rabbit (Hook and Hafez, 1968) the Tunica muscularis of the intramural part of the isthmus displays an additional inner longitudinal muscle layer. This layer is absent in the cheetah similar to the situation in the pig, dog (Hook and Hafez, 1968), and cat (Hafez and Black, 1969b;Bansal and Varinder, 2008).…”
Section: Microscopy Of the Isthmusmentioning
confidence: 99%
“…The uterine tube has a distance between the lumen mucosal surface and the serosal surface of only a few millimetres, and the uterine tube is known to be convoluted in nature. [1][2][3] To transverse this space for a distance of 2 cm by the Essure device without serosal perforation would be extraordinarily difficult as the length of the intramural portion of the fallopian tube is between 9 and 17 mm. 3 2 The laparoscopic finding demonstrated no outline of the device in the tube, and indeed even with palpation of the uterine tube, no device was seen or felt.…”
mentioning
confidence: 99%
“…[1][2][3] To transverse this space for a distance of 2 cm by the Essure device without serosal perforation would be extraordinarily difficult as the length of the intramural portion of the fallopian tube is between 9 and 17 mm. 3 2 The laparoscopic finding demonstrated no outline of the device in the tube, and indeed even with palpation of the uterine tube, no device was seen or felt. We would expect that if a perforation occurred between the mucosal surface and serosa with such a small distance between the two that an outline of the device would be seen and felt, hence it was more likely intratubal.…”
mentioning
confidence: 99%